i) Let the required harmonic function be F such that,
F(x,y)=X(x,t).Y(y,t).....(1)
As per the question the boundary condition are y>0,(0,0),to "e^{-\\lambda y}Cos\\lambda x,e^{-\\lambda y}{Sin\\lambda x}"
from equation 1..
we have
"\\frac{ d^2X}{ dx^2}+\\frac{d^2Y}{dy^2}=0"
The above equation can be written according to separation of variable
"\\frac{ d^2X}{ Xdx^2}=-\\frac{d^2Y}{Y dy^2}" = k"^2"
"\\frac{d^2X}{dx^2}=k^2x, \\frac{d^2Y}{dy^2}=-k^2y"
The solution of the above equation can be written as
X(x,t)="c_1coskx+c_2sinkx,Y(y,t)=c_3e^{kx}+c_4e^{ky}"
Then the harmonic function is given by,
"F(x,y)=(c_1coskx+c_2sinkx)(c_3e^{kx}+c_4e^{ky})"
This is the required function.
ii)As "x=e^{-\\lambda y}Cos\\lambda x"
y="x=e^{-\\lambda y}Sin\\lambda x"
then"\\frac{x^2}{x^2+y^2}=\\frac{e^{-2\\lambda y} Cos^2\\lambda x}{e^{-2\\lambda y} Cos^2\\lambda x+e^{-2\\lambda y} Sin^2\\lambda x}"
"\\frac{x^2}{x^2+y^2}=\\frac{e^{-2\\lambda y} Cos^2\\lambda x}{e^{-2\\lambda y} (Cos^2\\lambda x+ Sin^2\\lambda x)}"
"\\frac{x^2}{x^2+y^2}= Cos^2\\lambda x"
similiarly"\\frac{y^2}{x^2+y^2}=Sin^2\\lambda x"
Now the integrate both of the function with respect to "\\lambda"
"\\int\\frac{x^2}{x^2+y^2}d\\lambda=\\int Cos^2\\lambda d\\lambda=\\int (\\frac{1+Cos2\\lambda x}{2})d\\lambda"
="\\frac{\\lambda +\\frac{Sin2\\lambda x}{2x}}{2}"
Now integrate
"\\int\\frac{y^2}{x^2+y^2}d\\lambda=\\int Sin^2\\lambda d\\lambda"
="\\int (\\frac{1-Cos2\\lambda x}{2})d\\lambda"
="\\frac{\\lambda -\\frac{Sin2\\lambda x}{2x}}{2}"
These are the required functions.
Comments
Leave a comment